Knowledge Assessment about Deep Vein Thrombosis among Women Using Combined Oral Contraceptive Pills - Algethami, Abdulmajeed M.; Altowairqi, Aseel A.; Alqurashi, Lama S.; Almalki, Remas S. (International Journal of Innovative Research in Medical Science, 2025)
Background: Deep vein thrombosis (DVT) is a serious condition, and its risk is heightened among women using combined oral contraceptive pills (COCPs). However, awareness of this risk and knowledge of preventive measures vary significantly. Objective: This study aimed to assess the knowledge of DVT and its associated risks among women using COCPs in the Western region of Saudi Arabia. Methods: A cross-sectional study was conducted in the western region of Saudi Arabia among 380 women aged 18 years or older, who were current or previous COCP users. Participants with a history of DVT or vascular diseases were excluded. The study was conducted from February 2024 to November 2024. Data were collected using a validated questionnaire and analyzed using SPSS version 26, with statistical significance set at p < 0.05. Results: The participants had a mean age of 31.9 years.Most participants were from Taif (51.1%), married (87.4%), and held university degrees (67.9%). While 50.5% had heard of DVT, only 55% recognized the increased risk associated with COCP use. The majority (56.3%) relied on the internet for information, but 62.9% were unaware of preventive measures. The median knowledge score was 2 out of 4, with women from Makkah scoring significantly higher (P = 0.017). Conclusion: This study reveals moderate awareness of DVT among women using COCPs, highlighting significant gaps in knowledge regarding preventive measures. Educational interventions are needed to enhance awareness and encourage discussions about the associated risks with healthcare providers.